Analisis Faktor-Faktor Efektifitas Ekonomi Sirkular pada Program Bank Sampah Berdikari Joglo - Iis Permatasari; Suparno Suparno; Annisa Lutfia (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This study aims to analyze the direct impact of the circular economy on the Waste Bank program. It is expected to demonstrate community involvement in the program. Community participation and engagement in waste management initiatives can help reduce the environmental burden caused by waste hazards and also serve as business opportunities for the community. The study is based on several factors, including government policy, entrepreneurial knowledge, income expectations, and entrepreneurial attitude. Data were collected from 202 respondents through an online questionnaire and analyzed using the Structural Equation Modeling (SEM) method with a Partial Least Squares (PLS) approach. The results indicate that all variables examined in this study have a positive and significant influence on community participation.